(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Among various apple products, apple porridge is a much consumed product, not only for babies, but also for adults. It is a practical, healthy and tasty product that can be consumed throughout the day. However, it is an extremely perishable product. Therefore, the aim of this work was to evaluate the shelf-life period of apple porridge after the application of gamma radiation as a conservation technology. After the formulation of apple porridge was developed, which was subjected to gamma radiation at the dose of 1kGy in a dose tax of 0.356kGy.hour-1 and compared this treatment with the control (0kGy). From the results presented, it can be concluded that the period of conservation of apple porridge submitted to gamma radiation is 30 days. From the 60th day, the samples showed microbial growth, not being accepted for consumption. In comparison to the control, the use of gamma radiation was promising, since the standard sample showed contamination before 30 days. By the results it can be concluded that the dose used was adequate for the conservation of this product for the period evaluated.